Potential of Quercetin Compound from Guava Leaves (Psidium guajava L.) as a Inhibitor COVID-19 - Sengka, Rani; Rompegading, Andi Badli; Irfandi, Rizal; Nur, Muhammad; Arafah, Muhammad; Yani, Ahmad (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
This research is a computer-based experimental study using the molecular docking method of quercetin compounds in the leaves of the guava plant (Psidium guajava L.) against the target protein (receptor), namely Mpro SARS-CoV-2 (PDB ID: 6M2N) using various softwares. consists of Chem Draw Ultra version 7.0, Marvin Sketch, PLANTS, Yasara, Discovery Studio Visualizer 2021, and pkCSM online tool and, protox online tool. This study aims to find out how the potential  of the quercetin compound from the leaves of the guava plant (Psidium guajava L.) has on its ability to inhibit the spread of Covid-19 by molecular docking. Data analysis in this study was carried out based on data obtained from the analysis of pharmacokinetic profiles, physicochemical properties, molecular docking, and predictions of toxicity to compounds that have potential as drug ingredients. Based on the results of molecular docking, it was shown that the quercetin compound has the potential to act as an inhibitor of the Mpro receptor (PDB ID: 6M2N) as evidenced by the docking score obtained which is smaller than the docking score obtained by the original ligand of the target receptor.